Potencializando o ensino de geometria com o uso do Origami modular e o software Poly Pro na construção dos sólidos de Platão - Flôres, Jozeane Candido Moreira (2023)
This research had as its object of study the construction of actions with the intention of enhancing the learning of the content, in spatial geometry, of Plato's polyhedrons. For this purpose, it was supported by the mathematical software Poly Pro, in its version 1.12 together with the use of modular Origami. Such actions were developed in a class of 2nd year of high school of a school in the city of Rio Crespo/RO. Its theoretical foundation is in the socio-interactionist theory of Lev Vygotsky, mainly in his concepts of mediation, zone of proximal development and construction of scientific concepts. The research developed was of a quantitative and qualitative nature and had as its guiding question: Can the use of modular Origami and Poly Pro software assist the teaching process, and consequently, enhance the learning of spatial geometry in relation to Plato's solids? With the objective of providing conditions for the teaching of Plato's solids, through the insertion and practices of Origami, together with the Poly Pro software, with the intention of enhancing the learning of said content. The methodology was applied in three moments: 1st Conventional; 2nd Manipulative with Origami and, 3rd Use of Poly Pro software. As data collection instruments, questionnaires applied to students and records of the activities developed were used. To help other teachers carry out similar actions, the Educational Product "Polygami: A proposal for teaching the Geometry of Plato's polyhedrons using Poly Pro software and Modular Origami" was developed, available on the PPGECM page https://www.upf.br/ppgecm/dissertacoes-e-teses and Educapes http://educapes.capes.gov.br/handle/capes/743171. It was concluded at the end of this research that modular Origami and the Poly Pro software associated with the theme of the activity already mentioned, are enhancers for learning the geometric concepts involved in Plato's solids, as well as revealing how much the teacher is an active and transformative agent, responsible for enhancing the appropriation and use of tools and signs by the subjects researched.